PROFESIONALISME KERJA DAN KUALITAS PELAYANAN PT POS INDONESIA - Erna Sulistyanti Widodo (Institut Transportasi dan Logistik Trisakti, 2017)
The aim of this research is analyzing correlation between professionalism and service quality against the customer satisfaction. This research applied descriptive quantitative by using path analysis and regression analysis. This result shown us: 1) there is positive direct effect between professionalism against customer satisfaction. It shows that employee professionalism has positive impact to increase customer satisfaction. 2) there is positive direct effect between service quality against customer satisfaction. It shows that a good service quality will contribute positive impact to increase customer satisfaction. 3) there is positive direct effect between professionalism against service quality. This effect will show that implementation of professionalism has positive impact for better service quality.